Analisis Penentuan Jenis Pondasi Konstruksi Gedung Menggunakan Data CPT: Analysis Of Foundation Type Determination For Building Constructions Using CPT Data - Daud, Deasi Delfiani Anatasia Arisandi; Mauta, Matelda Christiana; Tuati, Anie Adrianti; Hayer, Yacob Victor (Media Ilmiah Teknik Sipil, 2025)
The increase in building infrastructure development in an area is certainly unavoidable. Soil, which is an important part of infrastructure development, certainly has provisions as a requirement to be used as a loan or good bearing capacity to receive the load above it so that it can maintain the stability of the construction above it. Not all soils have a stable bearing capacity for the construction above it. Soil investigations need to be used to determine the bearing capacity of the soil, so that the type of building construction foundation can be determined appropriately according to the CPT test data. The research location is in the Kupang Regency area and consists of 7 data collection locations. Soil physical test data is classified by AASTHO method and CPT test data is classified by soil type using qr and Fr relationship graph according to Robertson and Campanella and soil consistency according to Terzaghi and Peck. Based on the CPT data, the appropriate depth and type of foundation are determined. The CPT test results were then analysed to obtain the Permitted Bearing Capacityand Foundation Bearing Capacity values for each point. The analysis results show that all 7 locations have a foundation depth of ≥ 6 m and the appropriate foundation type is a mini pile foundation with a cylindrical size of Ø 0.50 m and a triangular size of 0.20 x 0.20 m.